The concept of poetry and its function according to the poets of Algeria Through the book "Algerian national poetry" For Ahmed Sharafi Al-Rifai - Boughouas, Zebida (Journal of Human Sciences, 2025)
Algerian poetry is a sincere expression of the political and national situation in general, and Algeria poets have taken great care of it, especially in the French colonial period, aware of the function of poetry in spreading awareness of these issues, and aspiring to liberation and achieving renaissance in all its fields, and this article dealt with this theme through a reading in the book "Algerian National Poetry" by Charfi Al-Rifai, where the importance of this choice comes from the fact that it stems from the chapters of the book that combined what is the history of Algerian poetry, He showed what is functional and artistic, depending on the descriptive approach, and reached conclusions including that Algerian poetry was a platform for expressing the cause of liberation, with awareness of the aesthetic function of poetry.